IoT: Based Solar Powered Water Pump System - Salman, Ratna Dewi; Lam, Hong Yin (Progress in Engineering Application and Technology, 2020)
IoT Based Solar Powered Water Pump System is project development of an automatic watering plant system that replaces the conventional watering plant. This project was focus on controlling the system by using is a mobile application called Blynk. The idea of the project is to help small farmers and users remotely controll and monitor their farm and remote workspace within a limited distance. Besides; remote monitoring, this project also provide automatic plant watering in order to reduce time-consuming activities at farm. This system used a solar panel as the main source which is connected to the solar charge controller in order to ensure the battery will not go overcharge and will act as the protection to the battery. IoT Based Solar Powered Water Pump System is created to improve the conventional system that is readily available by utilizing the different approach of an access system with the application of a Wi-Fi phone and solar system. In conclusion, : IoT based solar powered water pump system was successfully created and tested. This project provie proof of small scale concept which will help small farmers to replace the conventional ways of watering plant watering. Solar power offers sufficient amount of electricity to power up the system as well as the battery to ensure that the system is also operating during nigt hour without solar radiation energy.